Motilitas dan Viabilitas Spermatozoa Itik Lokal (Anas platyrhynchos) Setelah Penyimpanan Refrigerator dalam Ekstender Dikombinasi Berbagai Konsentrasi Krioprotektan Gliserol - Arie Amelia; Dadang Mulyadi Saleh; Hendro Pramono; Yulia Sistina (Fakultas Biologi | Universitas Jenderal Soedirman, 2013)
The economic value of ducks has increased one Day Old Duck in large quantities and short time, effects on artificial insemination technologies improvement. Spermatozoa used for artificial insemination, could be derived from sperm preservation biotechnology, by means to maintain or extend their viability and motility of those spermatozoa. Extenders and cryoprotectant are needed for maintaining sperm motility and viability during storage or preservation. This study aims to assess motility and viability of local ducks spermatozoa after six days srotrage in 3 different extenders (Ringer's lactate, Tris or PBS) in combination with 5 different concentrations (0, 2, 4, 6, and 8%) of cryoprotectant glycerol. Results showed that sperm motility and viability was very highly significant (P<0.01) different among treatments, extender factor as well as duration storage time also very highly significantly (P<0.01) affected motility and viability of treated sperm. However, glycerol concentration factor was not significant (P>0.05) affected motility and viability of the sperm. The best treatment, resulted in the highest percentage motility and viability of sperm with progressivity score >1, was the 8% glycerol in PBS storage for up to 2 days (75.00 ± 21.79% and 71.67±14.43%). This protocol could be applied in artificial insemination trial.